No ordinary assignment : a memoir - Ferguson, Jane, 1984- (Mariner Books, 2023)
"From award-winning journalist Jane Ferguson, an unflinching memoir of ambition and war-from the Troubles to the fall of Kabul. In Northern Ireland in the 1980s and '90s, war was a secret, and young Jane Ferguson wanted to know the truth. For her, war was called the Troubles, bomb threats and military checkpoints on the way to school were commonplace, and an uncle's gunshot wound in IRA crossfire was disguised as a cow kick. Jane developed a penchant for asking questions that cut through this culture of silence, while the unspoken tension in her village exploded into abuse and rage at home. An opportunity to study Arabic in Yemen after college came as a great relief, a ticket to a different, adventurous life-and to the very center of the story. Ferguson has since reported from nearly every war front around the globe-from Yemen and Syria during the Arab Spring, Afghanistan during the fall of Kabul, and Ukraine during Russia's 2022 invasion-but her rise to the highest ranks of journalism has been anything but ordinary. As a scrappy one-woman reporting team, a borrowed camera her only equipment, networks often told her she simply had the wrong accent, even the wrong appearance. Still, her ambition to build a life in journalism on her own terms thrust her into harm's way time and again. While other reporters chased "bang bang shoot 'em up" stories, a different set of questions guided Ferguson's work, ones that gave faces and names to the people experiencing these conflicts. In the face of grave violence and suffering, giving voice to civilian lives seemed a small act of justice, no matter the risks. For fans of Samantha Power, Marie Colvin, and Ariel Levy, Ferguson's bold debut chronicles her unlikely journey from bright, inquisitive child to intrepid war correspondent from the front lines of the most dangerous conflicts and dire humanitarian crises of our time. With an open-hearted humanity we rarely see in conflict stories, No Ordinary Assignment shows what it means to build an authentic career against the odds"--